Comparative effectiveness of the approaches to correct vascular structural and functional disturbances in postmenopausal women - S. N. Tolstov; V. B. Mychka; I. A. Salov; Yu. V. Prokhorova; V. A. Vyshivanyuk (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To compare the effects of Mildronate and hormone replacement therapy (HRT) with estradiol (1 mg) and drospirenone, DSPR (2 mg) on circadian blood pressure (BP) profile, arterial structure and function, and vascular stiffness parameters in women with early postmenopause and climacteric syndrome (CS). Material and methods. The study included 94 women with early postmenopause and CS, who provided written informed consent to participate and were divided into two groups. Group I included 36 women receiving Mildronate (500 mg twice a day), while Group II included 28 women who were administered, according to clinical indications, HRT (1 mg 17β-estradiol and 2 mg DRSP once a day). The control group (CG) included 30 women who did not receive either Mildronate or DRSP. At baseline and 16 weeks later, all participants underwent the assessment of blood biochemistry; intima-media thickness (IMT) of common carotid artery (CCA); endothelium-dependent vasodilatation (EDVD) of brachial artery (BA); antithrombogenic activity of vascular wall; aortal pulse wave velocity (aPWV); arterial stiffness; and 24-hour BP monitoring (BPM). Results. The study demonstrated positive effects of Mildronate therapy and HRT (1 mg 17β-estradiol and 2 mg DRSP) on metabolic status, circadian dynamics and variability (Var) of BP, and arterial structure and function. The largest positive changes in blood lipid profile were observed in Group I and II patients. By the end of the study, these patients demonstrated significantly decreased levels of systolic and diastolic BP and reduced BP Var, particularly in Group II. Mildronate therapy, but not HRT, was associated with normalisation of vascular wall antiaggregant potential. Group II demonstrated a significant reduction in CCA IMT levels, with a similar tendency in Group I. In both groups, the degree of endothelial dysfunction (ED) decreased, which was manifested in increased BA EDVD, decreased aPWV, and reduced arterial stiffness and was more pronounced in Group II. Conclusion. In menopausal women with CS, the effects of Mildronate and HRT on metabolic, structural, and functional disturbances were similar. Therefore, Mildronate therapy could be a new method of correction of these systemic disturbances.